Adverse effects of amphotericin B in children; a retrospective comparison of conventional and liposomal formulations. (1st March 2018) - Andrew, Eden C.; Curtis, Nigel; Coghlan, Ben; Cranswick, Noel; Gwee, Amanda
Abstract : Aims: Lipid formulations of amphotericin B, rather than conventional amphotericin (c‐amB), are increasingly used despite limited data comparing these preparations in children. Data on the incidence of adverse effects with amphotericin B at standard doses are scarce. This study aimed to compare the adverse effects associated with standard doses of c‐amB and liposomal amphotericin (l‐amB) in children. Methods: Children admitted to the Royal Children's Hospital Melbourne and treated with c‐amB or l‐amB between January 2010 and September 2013 were included. Clinical and laboratory data were retrospectively extracted from medical records to compare amphotericin‐related infusion reactions, nephrotoxicity (glomerulotoxicity and tubulopathy) and hepatotoxicity. Results: Seventy‐six children received c‐amB and 39 received l‐amB. Standard drug administration (recommended dose and infusion time) occurred in 74% (56/76) of patients on c‐amB and 85% (33/39) on l‐amB. In these 89 children, infusion‐related reactions were similar for both c‐amB and l‐amB (23% (13/56) vs. 9% (3/33); P = 0.15); none occurred in children aged <90 days. There was no difference in amphotericin‐associated glomerulotoxicity (c‐amB 14% (8/56) vs. l‐amB 21% (7/33); P = 0.40) or in the median maximum potassium requirements (c‐amB 3.1 vs. l‐amB 2.3 mmol kg −1 d −1 ; P = 0.29). Hepatotoxicity occurred more frequently with l‐amB than c‐amB (83% (24/29) vs. 56% (20/36); P = 0.032). Conclusions: When appropriately administered, l‐amB was associated with more hepatotoxicity than c‐amB, with no difference in infusion‐related reactions or nephrotoxicity. Differences in adverse effects between the preparations is not as marked in children as reported in adults.